Abortion in the Polish public discourse in the light of corpus research. A comparative approach - Szkudlarek-Śmiechowicz, Ewa (Papers in Linguistics, 2022)
The aim of the article is to determine differences in the construction of discourse on abortion in Poland over 30 years (from the 1990s to 2021) in the light of corpus research. Two reference corpora were used for the research (NKJP until 2010, MoncoPL from 2010) and two target corpora (weeklies: “Polityka”, “Tygodnik Powszechny”: 2020/2021). Collocations with the lexeme abortion and key words characterizing contemporary press discourse were analyzed quantitatively and qualitatively. The study of reference corpora showed a gradual increase in applications of means of polarizing discourse and rendering it more expressive, which are markers of the worldview of its participants. The study of target corpora indicated that the basic difference between them, which affects all the others, is related to the high textual and discursive importance of the lexeme law in “Polityka” and the lexeme church in “Tygodnik Powszechny”. It was also pointed out that abortion discourse of the recent months has focused on the activities of its subjects (protest, court sentence), and not on the topic of abortion in the strict sense.